Beyond antibiotics: leveraging microbiome diversity to combat antimicrobial resistance - Al-Kuwari, Ali; Al-Karbi, Hamad; Al-Khuzaei, Abdulla; Baroudi, Dounia; Bendriss, Ghizlane (Frontiers in Microbiomes, 2025)
The best way to fight harmful microbes may not lie in new antibiotics, but rather in leveraging the power of microbes themselves. Antimicrobial resistance (AMR) is a growing global concern, where the overuse of antibiotics has led to the emergence of resistant strains. This paper explores the potential of increasing diversity in gut microbiomes as natural approaches to fight AMR. The promotion microbial diversity is proposed as a promising strategy to reduce dependency on antibiotics by fostering a resilient microbial community. Strategies are discussed to address the loss of diversity caused by antibiotics including diet, probiotics, fecal transplants (FMT) and fermentation of animal/plant products. Preliminary findings from an experiment with camel milk fermentation suggest that fermentation can increase microbial diversity, potentially affecting resistance to common antibiotics such as tetracycline, streptomycin, penicillin, and chloramphenicol, and enhancing microbiome resilience, allowing it to naturally resist pathogens without additional antibiotic use. The results highlight both the benefits and potential risks fermented products. Additionally, FMT, naturally occurring in the animal world, is a promising method to restore microbiome balance and mitigating the impact of AMR. A mechanistic model is discussed to underscore the importance of maintaining microbial balance as an effective strategy for mitigating AMR and promoting long-term health. Further research are needed to better understand the mechanisms behind these changes and their implications for public health. This perspective paper calls for a shift in the approach to AMR, advocating for microbiome-based solutions as a sustainable alternative to traditional pharmaceutical interventions.